“Creciendo Juntos” Programme: Promoting Positive Relationships for Learners - Álamo-Muñoz, Adriana; Martín Quintana, Juan Carlos; Cruz-Sosa, Miriam del Mar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Schools can become positive environments by implementing evidence-based programmes. The aim of this article is to present the “Growing Together” programme and to analyse its effectiveness in promoting the establishment of positive relationships in schools. A sample of 990 students (=12.96; 47.5% girls) responded to the scale on students’ perception of their relationships at school and their level of educational participation (RMSEA=.049; 90% .043-.055; CFI=.976; TLI =.967 and SRMR=.026). While the control group worsens in their relationships and participation at school, the intervention group remains the same.